Open Source Hardware and Software Platform for Robotics and Artificial Intelligence - Ng Liang, Shing; K. O., Tan; T. H., Clement; T. H. , Lai; S. K., Ng (2015)
Recent developments in open source hardware and software platforms (Android, Arduino, Ubuntu etc.) have enabled rapid development of previously expensive and sophisticated system within a lower budget and atter learning curves for developers. Using these platform, we designed and developed a Java-based 3D robotic simulation system, with graph database, which is integrated in online and o line modes with an Android-Arduino based rubbish picking remote control car. The combination of the open source hardware and software system created a exible and expandable platform for further developments in the future, both in the software and hardware areas, in particular in combination with graph database for artificial intelligence, as well as more sophisticated hardware, such as legged or humanoid robots.